On Integrable Conditions of Generalized Almost Complex Structures (Communications in Mathematical Research, 2021)
Generalized complex geometry is a new kind of geometrical structure which containscomplex and symplectic geometry as its special cases. This paper gives the equivalence between theintegrable conditions of a generalized almost complex structure in big bracket formalism and thosein the general framework.
Keywords: generalized almost complex geometry; big bracket; supermanifold.